2017
DOI: 10.1016/j.ijsu.2016.09.083
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy versus thyroid lobectomy for papillary thyroid cancer: Comparative analysis after propensity score matching: A multicenter study

Abstract: Equivalent prognoses were observed for patients with 1- to 5-cm stage cN0 and cM0 PTC tumors treated by TL or TT after propensity score matching. Adverse events occurred less frequently in patients who underwent TL than TT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The recurrence rates at 5, 10, and 20 years were non-statistically different (1.9%, 4.3%, and 6.5% vs. 2.3%, 4.1%, and 5.9%, hemi- vs. total thyroidectomy, respectively), and no differences were seen for OS rates as well. Kuba et al [37] reported similar findings on 33 pairs of macroscopic PTC patients. The results of the above studies are in accordance with those reported by us.…”
Section: Discussionmentioning
confidence: 56%
“…The recurrence rates at 5, 10, and 20 years were non-statistically different (1.9%, 4.3%, and 6.5% vs. 2.3%, 4.1%, and 5.9%, hemi- vs. total thyroidectomy, respectively), and no differences were seen for OS rates as well. Kuba et al [37] reported similar findings on 33 pairs of macroscopic PTC patients. The results of the above studies are in accordance with those reported by us.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, Lee et al reported a 0.9% recurrence rate in the contralateral lobe, but 87% of the tumors in this study were micropapillary cancers [61]. Many retrospective studies, with various inclusion criteria, have reported global recurrence rates ranging from 4.2-7.1% after lobectomy for low-risk cancers [19,[62][63][64][65]. Contralateral thyroid nodules generally appear within five years of initial therapy [66].…”
Section: Oncologic Considerations: Recurrence In the Contralateral Lomentioning
confidence: 60%
“…There was no statistically significant difference of local recurrences in TL compared to TT, and distant metastases recurrence rates were higher in TT. Of note, only five studies [ 17 , 18 , 29 , 36 , 45 ] mentioned ultrasound as a routine preoperative assessment but only in patients evaluated since 2005 [ 43 ], while all studies also included patients who were treated before 2005. Thus, malignancies in the contralateral remnant lobe and small cervical lymph node metastases might have been missed, resulting in suboptimal treatment in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies do not report an association between tumor multicentricity and prognosis, thus the clinical significance of occult carcinoma is questionable [ 39 , 53 , 55 , 56 ]. Of the studies included in this meta-analysis that mentioned multicentricity, none showed an association between multicentricity and prognosis [ 17 , 18 , 29 , 37 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%